Teacher judgment accuracy regarding students' self-concepts: Affected by social and dimensional comparisons?. (June 2018) - Helm, Friederike; Müller-Kalthoff, Hanno; Mukowski, Rebecca; Möller, Jens
Abstract: Research on teacher judgment accuracy is connected with the Internal/External frame of reference model. Social and dimensional comparisons between achievements are central to the formation of students' mathematical and verbal self-concepts. Inferring self-concepts, teachers often ignore dimensional comparisons. Two studies tested whether information about students' achievements in two subjects can help teachers to comprehend students' social and dimensional comparisons, and to judge students' mathematics and German self-concepts more accurately. In Study 1 ( N = 35 teachers, N = 578 students), informed mathematics teachers judged mathematics self-concepts more accurately and showed stronger social comparison effects. Neither informed nor uninformed teachers showed contrastive dimensional comparisons. Study 2 ( N = 47, N = 746 students) replicated the central results of Study 1 for German teachers. Our results speak against contrastive dimensional comparisons in teachers' self-concept inferences. Yet, information about achievements can improve judgment accuracy through triggering stronger use of social comparison information. Highlights: Students compare their achievements socially and dimensionally. These comparisons affect students' mathematical and verbal self-concepts. Teachers informed about students' achievements strongly retrace social comparisons. Informed and uninformed teachers ignore dimensional comparisons. Informed teachers infer students' self-concepts more accurately.